Two new Chinese species of Tomocerus at different stages of troglomorphic adaptation (Collembola, Tomoceridae) - Yu, Daoyuan; Deharveng, Louis (Zootaxa, 2018)
Two new species of Tomocerus are described from caves in Guizhou and Guangxi Province, China. Tomocerus troglodytes sp. nov. is highly troglomorphic. It belongs to the kinoshitai complex, and is most similar to another eyeless and colourless species Tomocerus caecus, from which it differs as it has longer antennae; 2,2/2,2/2+2/0 versus 2,2/2,5/0/0 cephalic dorsal chaetotaxy formula; 6 versus 4 central macrochaetae on Th. II; 0 versus 2 ungual teeth; unguis devoid of baso-internal ridges; 3–5/3–5, I, 0–1, I versus 4–5/1–2,I–II,0–1,I–II dental spines formula; 2–4 versus 1 tenacular chaetae; and 0 versus 1 mucronal intermediate teeth. In contrast, Tomocerus leyensis sp. nov. is at an earlier stage of troglomorphic adaptation. It resembles several cave-dwelling species of the ocreatus complex in habitus and shape of dental spines, but differs in the following characters: absence of large postantennal organ; cephalic dorsal chaetotaxy formula 2/2,4/2+2/2+2 versus other patterns; larger number of ungual teeth; and only 1 large distal dental spine. The troglomorphic characteristics of the two species are discussed with emphasis on their potential adaptation to cave habitats.